The impact of foreign direct investment on economic growth: A comparative study of Ghana and Nigeria - Sani, Ali Ibrahim (2015)
The economic development performance can be used to measure the economic growth of a given country. In economic analysis, a country can attain economic growth through the growth in national income measurement. However, the role of foreign direct investment (FDI) on economic growth continues to be debated and tested in the literature on international economics and development economies. This paper extends the previous empirical studies on the issue by providing some evidence from time series data for the period 1971 to 2013 of Ghana and Nigeria. The primary objective of this study is to analyze the impact of FDI on economic growth of Ghana and Nigeria taking trade openness, Gross Fixed Capital Formation and human capital as control variables. To investigate the long run equilibrium relationship, Johansen and Juselius co-integration approach is analyzed, while the speed of adjustment in the short run is analyzed through the use of VECM method. In addition to check for the direction between FDI, T.OPEN, GFCF, HK and economic growth, granger causality test is performed for both Ghana and Nigeria. In Ghana, all the explanatory variables have long run relationship with economic growth. In Nigeria, FDI, GFCF and HK have long run relationship with economic growth. However, the VECM results in Ghana reveal that only T.OPEN and GFCF are statistically significant and therefore have short run relationship with economic growth. Similarly, the coefficient of ECM is statistically significant at 1% level of significance. Thus, 23.3% of the adjustment is achieved due to the correction of the adjustment speed in a year. In Nigeria, the coefficient of ECM is statistically significant at 1% level of significance. Thus, 10.8% of the adjustment is achieved due to the correction of the adjustment speed in a year. To this effect, Ghana‟s correction of the speed of adjustment in a year moves faster than that of Nigeria.